Punicalin Attenuates Breast Cancer-Associated Osteolysis by Inhibiting the NF-κB Signaling Pathway of Osteoclasts - Li, Tao; Jiang, Guangyao; Hu, Xuantao; Yang, Daishui; Tan, Tingting; Gao, Zhi; Chen, Zhuoyuan; Xiang, Cheng; Li, Shizhen; Ouyang, Zhengxiao; Guo, Xiaoning (Frontiers in Pharmacology, 2021)
Background: Breast cancer bone metastasis and osteoporosis are both severe diseases that seriously threaten human health. These diseases are closely associated with osteolytic lesions. And osteoclasts are the key targets of this pathological process. Given the lack of effective preventive or treatment options against these diseases, the exploitation of new pharmacological agents is critically required. Method: We assessed the efficacy of punicalin on receptor activator of nuclear factor-κB ligand (RANKL)-mediated osteoclast formation, F-actin ring formation, gene expression, bone resorption, nuclear factor-κB (NF-κB) as well as on mitogen-activated protein kinase (MAPK) signaling pathways and molecular docking in vitro. The impact of punicalin on breast cancer-induced osteoclastogenesis, breast cancer cell proliferation, and apoptosis were examined. Transwell assays were also performed. Moreover, we evaluated in vivo effects of punicalin in postmenopausal osteoporosis models and breast cancer bone metastasis model by micro-CT scanning and histomorphometry. Result: Punicalin inhibited osteoclast formation, F-actin ring formation, bone resorption, as well as osteoclast-related gene expression by suppressing the NF-κB signaling pathway. In vitro, punicalin also suppressed the breast cancer-induced osteoclastogenesis, and proliferation, migration as well as invasion of MDA-MB-231 cells and dose-dependently promoted their apoptosis. In vivo, punicalin significantly suppressed breast cancer-induced osteolysis, breast cancer-associated bone metastasis, and ovariectomized (OVX)-mediated osteoporosis by repressing osteoclast and breast cancer cell. Conclusion: Punicalin is expected to offer a novel treatment for the prevention of osteolysis diseases, including osteoporosis and breast cancer-associated osteolysis.